Exercise physiology : integrating theory and application - Kraemer, William J., 1953-; Deschenes, Michael R.; Fleck, Steven J., 1951- (Philadelphia : Wolters Kluwer, 2021)
This work captures the interest and excitement of undergraduate students in exercise and sport sciences. Renowned authors William Kraemer and Steve Fleck unite research and theory with real world application so students can easily relate to the concepts being presented.
Revision of: Exercise physiology : integrated from theory to practical applications.
Includes bibliographical references and index.
Keywords: Exercise -- Physiology -- Textbooks; Nutritional physiological phenomena -- Textbooks; Sports medicine -- Textbooks